Preparation and characterisation of epitaxial Pt/Cu/FeMn/Co thin films on (100)‐oriented MgO single crystals. Issue 10 (20th May 2015) - Schmidt, Mathias; Gräfe, Joachim; Audehm, Patrick; Phillipp, Fritz; Schütz, Gisela; Goering, Eberhard
<x xml:space="preserve">Abstract</x> FeMn/Co thin‐films, a purely metallic exchange‐bias system, were prepared on (100)‐oriented MgO single crystals. The layers were grown by molecular beam epitaxy (MBE). The crystalline and magnetic properties could be tuned by using sputtered Pt buffer layers deposited at variable temperatures. A transition of the crystalline orientation from (111)‐terminated layers at lower deposition temperatures to (100)‐terminated layers at temperatures higher than 950 K was established and the impact on the magnetic sample properties was investigated. Here, the detailed sample preparation process is shown together with low energy electron diffraction (LEED), medium energy electron diffraction (MEED), atomic force microscopy (AFM), X‐ray photoelectron spectroscopy (XPS), X‐ray diffraction (XRD) and transmission electron microscopy (TEM) measurements revealing the samples structure and composition. The crystalline orientation of Pt was imprinted to the magnetic layer stack and clearly influenced the exchange‐bias (EB) and coercive field (HC) as shown by superconducting quantum interference device (SQUID) and magneto‐optical Kerr effect (MOKE) measurements. Furthermore, a correlation between the crystallite size and the temperature dependent magnetic properties could be identified.